Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pcbi.1005795
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolving sequence features that discriminate between overlapping regulatory annotations

Abstract: Genomic loci with regulatory potential can be annotated with various properties. For example, genomic sites bound by a given transcription factor (TF) can be divided according to whether they are proximal or distal to known promoters. Sites can be further labeled according to the cell types and conditions in which they are active. Given such a collection of labeled sites, it is natural to ask what sequence features are associated with each annotation label. However, discovering such label-specific sequence fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…This systematic analysis of transitions in epigenetic states across cell types helps uncover the differentiation history of cCREs and provides mechanistic insights into regulation. For example, by using SeqUnwinder (Kakumanu et al 2017) to discover discriminative motifs, we found that the CMP cCREs that transition from poised to active enhancer in the erythroid lineage were enriched for the GATA transcription factor binding site motif, whereas those that transition to a polycomb state were enriched in motifs for binding ETS transcription factors such as SPI1 (also known as PU.1) (Supplemental Fig. S13).…”
Section: Epigenetic States Of Ccres Vary Across Cell Types In An Infomentioning
confidence: 99%
“…This systematic analysis of transitions in epigenetic states across cell types helps uncover the differentiation history of cCREs and provides mechanistic insights into regulation. For example, by using SeqUnwinder (Kakumanu et al 2017) to discover discriminative motifs, we found that the CMP cCREs that transition from poised to active enhancer in the erythroid lineage were enriched for the GATA transcription factor binding site motif, whereas those that transition to a polycomb state were enriched in motifs for binding ETS transcription factors such as SPI1 (also known as PU.1) (Supplemental Fig. S13).…”
Section: Epigenetic States Of Ccres Vary Across Cell Types In An Infomentioning
confidence: 99%
“…This systematic analysis of transitions in epigenetic states across cell types helps uncover the differentiation history of cCREs and provides mechanistic insights into regulation. For example, using SeqUnwinder (Kakumanu et al 2017) to discover discriminative motifs, we found that the CMP cCREs that transition from poised to active enhancer in the erythroid lineage were enriched for the GATA transcription factor binding site motif, whereas those that transition to a polycomb state were enriched in motifs for binding ETS transcription factors such as PU.1 (Supplemental Fig. S14).…”
Section: Epigenetic States Of Ccres Vary Across Cell Types In An Infomentioning
confidence: 99%
“…To overcome the local behavior of such attribution methods, we extracted 20 bp sequences surrounding the local IG peaks; i.e., we extracted regions or "hills" that drive the neural network output from each sequence bound by Ascl1. We clustered the IG-derived hills based on their underlying sequence features using a K-means based clustering procedure described previously in SeqUnwinder 69 . Briefly, only k-mers present in at least 5% of IG-derived hills are used for clustering, and K-means clustering is performed using Euclidean distance as a metric 69 .…”
Section: Feature Attribution With Integrated Gradientsmentioning
confidence: 99%
“…We clustered the IG-derived hills based on their underlying sequence features using a K-means based clustering procedure described previously in SeqUnwinder 69 . Briefly, only k-mers present in at least 5% of IG-derived hills are used for clustering, and K-means clustering is performed using Euclidean distance as a metric 69 . We then perform motif discovery using MEME 70 to identify the enriched motifs within each K-means defined cluster 69 .…”
Section: Feature Attribution With Integrated Gradientsmentioning
confidence: 99%
See 1 more Smart Citation